2016
DOI: 10.1007/s00068-016-0689-y
|View full text |Cite
|
Sign up to set email alerts
|

Gustilo type IIIC open tibia fractures with vascular repair: minimum 2-year follow-up

Abstract: Scoring systems and the ischemic time are not the only predictors of amputation. The decision of the treatment mode should be made by the patient and the care team after discussing the options and outcomes rather than relying on a scoring system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…However, according to several reports, limb salvage is more desirable than amputation in terms of psychological and long-term functional prognoses. By contrast, other reports have suggested that the time required by patients to return to work and hospitalization period are similar between the two interventions [1][2][3][9][10][11]. A meta-analysis showed that limb salvage and amputation are functionally equivalent, but limb salvage is the more psychologically acceptable approach [9]; this is consistent with another study that claimed amputation is more di cult to accept psychologically than salvage [3].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, according to several reports, limb salvage is more desirable than amputation in terms of psychological and long-term functional prognoses. By contrast, other reports have suggested that the time required by patients to return to work and hospitalization period are similar between the two interventions [1][2][3][9][10][11]. A meta-analysis showed that limb salvage and amputation are functionally equivalent, but limb salvage is the more psychologically acceptable approach [9]; this is consistent with another study that claimed amputation is more di cult to accept psychologically than salvage [3].…”
Section: Discussionsupporting
confidence: 61%
“…A meta-analysis showed that limb salvage and amputation are functionally equivalent, but limb salvage is the more psychologically acceptable approach [9]; this is consistent with another study that claimed amputation is more di cult to accept psychologically than salvage [3]. Most patients with salvaged limbs face problems in their daily lives owing to a limited range of motion, but none want amputation as an intervention [11]. A previous study showed no signi cant difference in the functional outcomes between the limb salvage and amputation groups for at least 7 years [1].…”
Section: Discussionmentioning
confidence: 55%
“…[ 3 ] Attempted limb salvage has a higher risk for a longer hospital stay, more expense, a greater number of surgeries, and significantly higher rates of complications. [ 1 3 , 7 ] However, some patients may undergo secondary amputation because of failure in limb salvage. The reported rate of amputation is as high as 78%, [ 8 ] and the secondary amputation rate reaches 15% in grade IIIC fractures of the lower limb.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Predicting which patients should forego limb salvage and undergo amputation is a challenge to surgeons. Many investigators have reported on various amputation predictors for patients with grade IIIA or grade IIIB fractures of the lower limb, [ 1 , 2 , 9 , 10 ] but there are comparatively few studies on grade IIIC fractures of the lower limb. The aim of this study was to gather cases in our hospital and analyze the amputation predictors for patients with severe lower limb injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation